Numerical simulation and experiments to improve throwing power for practical PCB through-holes plating. Issue 4 (4th November 2019) - Xiang, Jing; Wang, Chong; Chen, Yuanming; Xia, Feng; He, Wei; Mao, Hua; Zhou, Jinqun; Chen, Qingguo; Jin, Xiaofeng
Abstract : Purpose: The synergism of convection, current density distribution and additives are investigated by numerical simulation and electrochemical experiments to understand the throwing power (TP) of copper electro-deposition for different aspect ratio ( AR ) and plating difficulty (Dif ) of through-holes ( THs ) in printed circuit board ( PCB ) manufacture. Design/methodology/approach: The flow field of THs and current density distribution on various AR of THs are calculated and analyzed. Meanwhile, corresponding simulation is used to study the performance of plating electrolytes on TP. Two electrochemical parameters, overpotential ( η ) and potential difference (△ η ), are chosen to evaluate the electrochemical properties of different plating solutions by galvanostatic measurement and potentiodynamic cathode polarization at different rotating speeds. Findings: By combining both the results of simulation and practical plating, these two electrochemical properties of electrolytes exhibit significant impact to the system at varied conditions. Especially, the electrolyte with higher polarizing η and △ η values lead to the elevated TP for AR of more than 2:1. Originality/value: The harring cell model, we build a bridge between the theoretical and experimental study for control of uniformity of plating THs in PCB manufacturing. This dual-parameter evaluation is validated to be a promising decisive method to guide the THs plating with particular AR in industry.